กระบวนการสื่อสารเพื่อสร้างเครือข่ายพันธมิตรที่สัมฤทธิ์ผลในธุรกิจประกันชีวิต - วรวรรณ อารีประชาภิรมย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
This study explores communication process of insurance agent networking and other communication factors leading to success in expanding partnership networking. In-depth interview was conducted with insurance agents, Insurance companies executives and the Thai Life Underwriter Association executives. The research reveals that communication process for insurance agent networking is horizontal. Leader is the core of the network. The communication style is divided into two parts: communication within the group and communication between groups. Communication within the group appears with three styles: (1) One-way communication, (2) Formal two-way communication, (3) Informal two-way communication. Communication between groups also characterizes 3 styles : (1) Communication between insurance agents and Insurance companies (2) Communication between insurance companies and the Thai Life Underwriter Association, (3) Communication between insurance agents and the Thai Life Underwriter Association. There are five communication factors essentially affecting the development of insurance agent networking. Those are sender, insurance essence, communication channel, receiver and social factors.